Regional Competitiveness of a Tourism Cluster: A Conceptual Model Proposal - Ferreira,João M. (2009)
Tourism is characterized for being a sector that has been highlighted as one of the activities with greatest potential for expansion on a global scale. For its growth potential and for being a product that can only be consumed in loco, tourism accepts the prominence role of being a strategy for local development. In this context the search for competitiveness is one of the key concerns of companies around the world. As clusters being a competent tool in companies performance, in regional development and in countries competitiveness, it is important to analyze its potential in tourism. This research aims to propose a conceptual model to analyze how a tourism cluster encourages its regional competitiveness.